Inferring health claims: a case study - Green, David W. (International Journal of Speech, Language and the Law, 1996)
Advertisements and packaging material are frequently designed to elicit consumer inferences, some of which may be legally proscribed. This paper discusses the analysis of such inferences and the empirical resting of analytic results. By way of a case study, it reports the analysis and empirical testing of the inferences elicited by two different packages on the same breakfast cereal. Analysis on the first package indicated that consumers might draw a legally proscribed inference (the prevention claim) that eating the product would reduce the risk of heart disease. In contrast, analysis of the second package indicated that such an inference might nor be drawn. Two empirical studies supported the analytic findings. Individuals having read and looked at a black and white copy of either the first or the second package were asked a number of questions. In particular, they were asked to write down what they perceived as the benefit or benefits of eating the product. More subjects reading the first package responded the prevention claim. The second study also required subjects to draw causal diagrams of the factors influencing the risk of heart disease. These diagrams confirmed that the failure to infer the prevention claim was nor attributable to a lack of knowledge of the connection between cholesterol and heart disease, bur to the absence of any mention of this connection in the next. In addition, the empirical data point up the role of visual imagery in guiding the inferences drawn.